The Influence of Online Customer Reviews and Online Customer Ratings on Purchasing Decisions Product electronics in the Shopee marketplace for the Karawang Regency Community - Aries Budiman; Nelly Martini (Primanomics : Jurnal Ekonomi & Bisnis, 2023)
This research aims/objectives of this research are to find out, analyze, explain online customer reviews about selling electronic products in the shoppee marketplace, online customer ratings about selling electronic products in the shoppee marketplace, purchasing decisions of electronic products in the shoppee marketplace, the relationship between online customer reviews with online customer ratings on selling electronic products in the shoppee marketplace, the effect of partial online customer reviews on purchasing decisions of electronic products in the shopee marketplace, the effect of stimulants between online customer reviews and online customer ratings on buying electronic product decisions in the shoppee marketplace. This research was conducted using quantitative methods with descriptive and verification approaches and sampling using the Malhotra sampling technique which resulted in a sample of 115 respondents. The analysis technique used is the Likert scale analysis technique and path analysis with the help of the sequential interval method (MSI), Microsoft Office, and SPSS version 26. 0. Based on the results of the analysis that has been carried out, this research proves that. The correlation coefficient between the variables Online Customer Review and Online Customer Rating obtained a value of 0.661 which means that it is quite strong, positive and significant between online customer reviews and online customer ratings. the partial effect of online customer reviews on purchasing decisions has a value of 27.8%. The effect of online customer ratings on purchasing decisions has a value of 42.0%. The simultaneous effect of online customer review and online customer rating is 69.8% while the remaining 30.2% is another variable not examined.